Munidopsis antonii - Baba, Keiji; Macpherson, Enrique; Poore, Gary C. B.; Ahyong, Shane T.; Bermudez, Adriana; Cabezas, Patricia; Lin, Chia-Wei; Nizinski, Martha; Rodrigues, Celso; Schnabel, Kareen E. (Zenodo, 2008)
Munidopsis antonii (Filhol, 1884) Galathodes antonii Filhol, 1884: 230, fig. 2 (NE of Azores, 3975–4010 m). Munidopsis antonii . — Henderson, 1888: 151, pl. 18, figs 1, 1a (SW of Australia, and off Juan Fernandez, 2516–3294 m). — Luke, 1977: 28 (list; Baja California, Basin off Bahia Magdalena, and off St San Juan, Peru, 3427–3676 m). — Baba, 1982a: 113, pl. 1, fig. 2 (Izu Shoto, Japan, 3420–3960 m)). — de Saint Laurent, 1985: table 2 (Bay of Biscay, 3992–4510 m). — Hendrickx & Harvey, 1999: 376 (list). — d'Udekem d'Acoz, 1999: 166 (review of occurrences). — Davie, 2002: 65 (no record). — Baba, 2005: 284 (132, 284, figs 52–54 (Mozambique Channel, off Sri Lanka, Tasman Sea, off Zamboanga, W of Costa Rica, and Gulf of Panama, 3660–3800 m, key, synonymies). — Macpherson & Segonzac, 2005: 14 (NE Atlantic, off Namibia, Gulf of Guinea, off South Africa, Azores, NW Atlantic, Bay of Biscay, 3134–4460). — Macpherson, 2007: 38 (west of Sri Lanka, 3450–3625 m). — Jones & Macpherson, 2007: 480 (off California, 4100 m). — Osawa & Takeda, 2007: 137, fig. 3C, D (south of Tosa Bay, 2739–3278 m). Munidopsis Antonii . — A. Milne Edwards & Bouvier, 1900: 321, pl. 4, fig. 2, pl. 30, figs 20–24 (N and NE of Azores, 3975–4010 m). — Hansen, 1908: 38, pl. 3, figs 3a, 3b (southern part of Davis Straits, 2626 m). — Bouvier, 1922: 47 (Bay of Biscay, 3910 m). Munidopsis beringana Benedict, 1902: 279, fig. 23 (type locality: Bering Sea, [55°23´00”N, 170°31´00”W], 3241 m [3 female syntypes, USNM 20557]). — Rathbun, 1904: 167 (no record). — Makarov, 1938: 101, fig. 36 (Sea of Okhotsk, 3500 m). — Ambler, 1980: 24 (Cascadia Basin and Tufts Plain off Oregon, 2800–3990 m). — Wicksten, 1989: 315 (list). — Chevaldonné & Olu, 1996: 290 (no record). — Martin & Haney, 2005: 478 (hydrothermal vents and cold seeps review). Munidopsis antoni [lapsus]. — Haig, 1955: 40 (no record). — Andrade, 1985: 111 (Juan Fernandez islands). Type data: syntypes, 2 males, MNHN Ga 277 and 278; 1 ovigerous female, USNM 22909. Type locality: NE ...